Comparison of Experimental and Computational Heat Transfer Characterization of Water Jet Impingement Array with Interspersed Fluid Extraction. Issue 6 (26th March 2021) - Hobby, David; Walker, Tom; Rattner, Alex; Jacobsen, Chris; Sherrer, David; Bandhauer, Todd
Abstract: A jet impingement cooling device was designed with jet-adjacent fluid extraction ports distributed throughout the impingement array. The device was fabricated from a photopolymer material using a three-dimensional printing technique and tested for flow resistance and cooling performance using water as the working fluid. Parallel to physical experiments, computational simulations were performed using a quarter-jet repeating unit cell consistent with the physical device geometry, but independent of the manifold architecture. Pressure drop and heat transfer results from both methods were evaluated and compared. It was found that the computational and experimental pressure drop results showed excellent agreement after manifold pressure drops were properly accounted for using a reduced-order analytical model. Heat transfer results were shown to have reasonable agreement with differing trends. A discussion on possible causes for the difference is presented and suggestions are made for future accommodation. Finally, this work proposes a strategy for development of broadly applicable thermal and pressure drop correlations which span a wide range of geometries, fluid properties, heat fluxes, and flow parameters.